Design, development, and evaluation of the Robobug board game: an unplugged approach to computational thinking - Chong, Sin Yoon; Md Khambari, Mas Nida (International Association of Online Engineering (IAOE), 2022)
This paper presents the design, development, and evaluation of the Robobug board game, which was developed to foster computational thinking (CT) among primary school pupils in Malaysia, particularly those who encounter computer and Internet access issues. Utilizing Richey and Klein's design and development (DDR) methodologies, this research serves as a primer by first concentrating on needs analysis for the design, then converting it into the development of the board game. The focus of this study was on how the design aspects of Robobug might help children grasp CT principles and foster CT practices. The Robobug board game was initially assessed remotely via questionnaire by a panel of eight subject matter experts from Malaysian institutions. Using the questionnaire and evaluation rubrics, experts were asked to offer insights with the following objectives: (i) to evaluate the design features; (ii) to examine the computational concepts; and (iii) to examine the computational practices of the Robobug board game. The research found that the Robobug board game has significant potential for use as an unplugged tool and alternative technique for instructors to enhance CT abilities outside the typical classroom. Additionally, it can be utilized to incorporate collaborative and game-based learning into teachers' instructional strategies to boost student engagement and achievement. The Robobug board game's shortcomings and suggestions for improvement are discussed.